Complications of high myopia: An update from clinical manifestations to underlying mechanisms - Du, Yu; Meng, Jiaqi; He, Wenwen; Qi, Jiao; Lu, Yi; Zhu, Xiangjia (Advances in ophthalmology practice and research, 2024)
High myopia is one of the major causes of visual impairment and has an ever-increasing prevalence, especially in East Asia. It is characterized by excessive axial elongation, leading to various blinding complications that extend beyond mere refractive errors and persist immovably after refractive surgery, presenting substantial public health challenge. High myopia-related complications include lens pathologies, atrophic and tractional maculopathy, choroidal neovascularization, peripheral retinal degenerations and retinal detachment, and glaucoma and heightened susceptibility to intraocular pressure (IOP) elevation. Pathological lens changes characteristic of high myopia include early cataractogenesis, overgrowth of lens, weakened zonules, and postoperative capsular contraction syndrome, possibly driven by inflammatory pathogenesis, etc. Dome-shaped macula and cilioretinal arteries are two newly identified protective factors for central vision of highly myopic patients. These patients also face risks of open-angle glaucoma and IOP spike following intraocular surgery. Morphologic alternations of optic nerve in high myopia can complicate early glaucoma detection, necessitating comprehensive examinations and close follow-up. Anatomically, thinner trabecular meshwork increases this risk; conversely lamina cribrosa defects may offer a fluid outlet, potentially mitigating the pressure. Notably, anxiety has emerged as the first recognized extra-ocular complication in high myopia, with an underlying inflammatory pathogenesis that connects visual stimulus, blood and brain. High myopia induces multiple ocular and potential mental health complications, underscoring the need to develop more effective strategies to improve both physical and emotional well-being of these patients, among which anti-inflammation might possibly represent a promising new target.